Cassava breeding and varietal dissemination in Thailand: Major achievements during the past 25 years - Sarakarn, Supachai; Limsila, Atchara; Watananonta, Watana; Suparhan, Danai; Suriyapan, Preecha (International Center for Tropical Agriculture, 2001)
The cassava breeding program in Thailand started with the hybridization of local clones, followed by selection, at the Rayong Field Crops Research Center in 1975, and at Sri Racha Research Station of Kasetsart University in 1983. During this initial period of recombining genes available from a narrow genetic base, progress in yield improvement was limited. In 1983, CIAT established its Asian Regional Program in Thailand. CIAT’s role in Thailand has been mainly to supply cassava germplasm from Latin America to this country, in order to increase the genetic variability of parental lines and to help develop an efficient and highly effective scheme of hybridization and continuous selection of this germplasm. The Thai germplasm collection also included earlier introductions from the Virgin Islands and Indonesia. This collaborative effort resulted in the official release of six new cassava cultivars during the period 1983-1993: four from the Department of Agriculture (DOA) and two from Kasetsart University. These new cultivars are characterized by high yield capacity, high harvest index, high root starch content and early harvestability. In 1999, DOA released a new cultivar specifically for planting in the northeastern part of the country; it was named Rayong 72. Regarding varietal dissemination, in 1994 the government established a special program for the rapid multiplication of new recommended cassava cultivars to replace the local cultivar, Rayong 1. This program involved the cooperation of DOA and Kasetsart University for supplying basic planting material, as well as the Department of Agricultural Extension and the Thai Tapioca Development Institute for multiplication and distribution of this material. The success achieved by this program can be gauged by the fact that by 1997 about 64% of the cassava area in Thailand was planted to the new recommended cultivars.